Picture Book Legenda Ki Rangga Gading Sebagai Media Pembelajaran Anak (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
Along with the development of the era of oral folklore fading, causing many children who do not recognize it. Therefore, the artist takes a Thesis on the Creation of Fine Art Works with the title "Picture Book of West Java Legends as Learning Media for Children (Edition: Ki Rangga Gading)". With the aim of bringing legends from the Tasikmalaya area, West Java to the wider community, creating an innovative and interactive picture book. This study uses a qualitative method. Data were collected by means of documentation, observation, and also questionnaires. Then the results of the data are analyzed. The conclusion of the research results based on the analysis of the work, the strength of the artist's work is in the illustration style with digital painting techniques, using attractive colors, by showing the expressions of the characters, showing the characteristics of Sundanese cultural characteristics. Using a pop-up page technique. This technique is dominated by illustrations or pictures with a little story text with a visual appearance that is more dimensional to make it more real by the surprises that are given on each page, commonly called "children's books". So that it can attract children's reading interest and learning media for children, to get to know Indonesian ethnicities and culture, especially West Java.